Pre-Clinical Mouse Models of Human Prostate Cancer and their Utility in Drug Discovery - Park, Serk In (2010)
In vivo animal experiments are essential to current prostate cancer research, and are particularly critical to studying interactions between tumor cells and their microenvironment. Numerous pre-clinical animal models of prostate cancer are currently available, including transgenic mouse models and human prostate cancer xenograft mouse models. In contrast to transgenic mouse models producing more heterogeneous cohorts of tumors, xenograft mouse models provide more controlled approaches. This unit describes the detailed procedures necessary to establish several distinct pre-clinical mouse models of human prostate cancer, including an orthotopic prostate xenograft model, an orthotopic bone metastasis model, an experimental metastasis model of intra-cardiac injection, and a vossicle model of tumor-bone interaction.